Effects of soy protein isolate hydrolysates on cholecystokinin released by rat intestinal mucosal cells and food intake in rats - Yang, Yang (J Food Sci Technol, 2020)
Soy protein isolate hydrolysates (SPIH) were prepared from soy protein isolate (SPI). Effects of SPIH on a satiety signal cholecystokinin (CCK) and feeding behavior in rats were investigated. SPIH induced more CCK release (164.66 ± 2.40 pg/mL) by rat intestinal mucosal cells than SPI (143.33 ± 3.71 pg/mL). Meal size (MS), intermeal interval (IMI), and satiety ratio (SR = MS/IMI) of rats received different daily doses of SPIH or dietary fiber were detected for 40 days. A 100 mg/kg dose of SPIH resulted in a greater SR than an identical dose of dietary fiber, while a 300 mg/kg dose resulted in a less MS and IMI. A 500 mg/kg dose of SPIH had similar effects to the same dose of dietary fiber on reducing MS, extending IMI, and increasing SR, but resulted in a significantly less body weight at the end of the experiment (318.15 ± 17.83 g) than the dietary fiber group (340.28 ± 6.15 g).